Penerapan Teori Pemidanaan terhadap Pelaku Tindak Pidana Tanpa Hak atau Melawan Hukum Memiliki Narkotika Golongan I (Studi Kasus Putusan Pengadilan Negeri Jakarta Selatan Nomor 700/PID.SUS/2023/PN.JKT.SEL) - Bata, Ezekiel; Cahyo, Cahyo (FOCUS, 2025)
Category I narcotics are regulated under Law Number 35 of 2009 concerning Narcotics. These substances have a high potential for addiction and pose serious health risks, which is why their use is strictly limited. This study examines the legal enforcement against individuals unlawfully possessing non-plant Category I narcotics weighing more than 5 grams, as well as the legal reasoning behind the Panel of Judges' decision in Case No. 700/Pid.Sus/2023/PN.Jkt.Sel.. The legal provisions applicable in such cases are found in Articles 112(2) and 114(2) of Law No. 35/2009. The penalties include the death penalty, life imprisonment, or imprisonment ranging from 6 to 20 years, along with fines from IDR 1 billion to IDR 10 billion. In this case, the judge concluded that all elements of Article 112(2) had been fulfilled, leading to the defendant being lawfully and convincingly proven guilty as charged in the second alternative indictment. Beyond the legal framework, the judge also considered aggravating and mitigating circumstances. The widespread abuse of narcotics is a complex issue that requires collaboration between the government, law enforcement, society, and families. Consistent preventive, repressive, and rehabilitative measures are key to reducing drug abuse. Education, rehabilitation, and strict law enforcement must go hand in hand to create a society free from the dangers of narcotics.